On the structure of the totally ordered set of unimodal cycles - Irene Mulvey (International Journal of Mathematics and Mathematical Sciences)
We continue the study of a class of unimodal cycles where each cycle in the class is forced by every unimodal cycle not in the class. For every order, we identify the cycle in the class of that order, which is maximal with respect to the forcing relation.